1988
DOI: 10.1055/s-2006-962336
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil ofAgeratum conyzoides

Abstract: The essential oil of AGERATUM CONYZOIDES leaves was analysed by means of GC-MS and associated procedures. Fifty-one constituents - 13 monoterpenoid hydrocarbons (5.0%), 7 oxygenated monoterpenoids (1.4%), 16 sesquiterpenoid hydrocarbons (4.3%), 4 oxygenated sesquiterpenoids (0.8%), 3 phenylpropanoids and benzenoids (2.33%), 6 chromenes (85.2%), and 2 chromans (0.9%) - were identified. Only six of these components have been previously found in AGERATUM essential oil. The natural occurrence of the two chromans:6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0
4

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 13 publications
5
47
0
4
Order By: Relevance
“…9,10 Several other secondary metabolites such as lignans, steroids, chromenes and chromene dimers have also been reported as chemical constituents of organic solvent extracts of A. houstonianum and A. conyzoides, 11,12 however, the identification of precocenes as the major volatile components of A. conyzoides from Brazil is in accordance with previous investigations reported on A. conyzoides from many countries, and also on other species of the genus Ageratum, such as A. houstonianum and A. mexicanum. 13,14 On the other hand, a rich monoterpene fraction with β-myrcene as the major compound was observed for Ac.…”
supporting
confidence: 88%
“…9,10 Several other secondary metabolites such as lignans, steroids, chromenes and chromene dimers have also been reported as chemical constituents of organic solvent extracts of A. houstonianum and A. conyzoides, 11,12 however, the identification of precocenes as the major volatile components of A. conyzoides from Brazil is in accordance with previous investigations reported on A. conyzoides from many countries, and also on other species of the genus Ageratum, such as A. houstonianum and A. mexicanum. 13,14 On the other hand, a rich monoterpene fraction with β-myrcene as the major compound was observed for Ac.…”
supporting
confidence: 88%
“…Durodola (1977) Ageratum conyzoides (goat weed) effect on serum protein and enzyme levels analgesic, astringent and haemostatic activities. Ekundayo et al (1988) reported that the essential oil of the plant also possess significant antibiotic activity and is commonly used in treating local infections.…”
Section: Discussionmentioning
confidence: 99%
“…The use of this herb as a bacteriocide, antidysentric and antibiotic has been reported for communities in Asia, Africa, India and South America (Almagboul, 1985;Ekundayo et al, 1988;Borthakar and Baruah, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical compositions of the EOs extracted from the leaves of A. conyzoides acclimatized in the western zone of Africa display a similar pattern. The leaves of Ghanaian plants contain 80.3% of precocene I [40], while those from Burkina-Faso, Benin, Lagos and Ibadan (Nigeria) respectively contain 86.0% [41], 85.6%, 63.1% [42] and 82.2% [43]. The EO exhibited remarkable insecticidal activity-against the cowpea weevil, Callosobruchus maculatus F. [44].…”
Section: Introductionmentioning
confidence: 99%